2013
DOI: 10.1002/pd.4176
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis, clinical outcomes, and associated pathology in pregnancies complicated by massive subchorionic thrombohematoma (Breus' mole)

Abstract: Massive subchorionic thrombohematoma/Breus' mole may be diagnosed in the second trimester by ultrasound assessment of the placenta. Normal fetal growth and UA Doppler waveforms are associated with perinatal survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…In addition, massive subchorionic hematoma/thrombohematoma (the so-called ‘Breus’ mole’, a hematoma placed beneath the chorionic plate separating it from the underlying intervillous space and must be more than 1 cm thick), different from those two hematomas [11][13], was also excluded in our review. Search term combination for bibliographic databases was text words, including the following variations of search terms combing with pregnancy outcome: intrauterine/subchorionic/retroplacental/subplacental hematoma/hemorrhage/bleeding/collection/fluid.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, massive subchorionic hematoma/thrombohematoma (the so-called ‘Breus’ mole’, a hematoma placed beneath the chorionic plate separating it from the underlying intervillous space and must be more than 1 cm thick), different from those two hematomas [11][13], was also excluded in our review. Search term combination for bibliographic databases was text words, including the following variations of search terms combing with pregnancy outcome: intrauterine/subchorionic/retroplacental/subplacental hematoma/hemorrhage/bleeding/collection/fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the ultrasound findings of MSH are highly variable, and the pregnancy outcome is poor. Table shows the results of a literature review performed by searching MEDLINE for “massive subchorionic hematoma” and/or “Breus’ mole” published in English after 2000 . There were 43 cases, including the case outlined here.…”
Section: Discussionmentioning
confidence: 99%
“…FGR occurs due to utero‐placental insufficiency, and when a hematoma occurs near the umbilical cord attachment, the umbilical vessels can be compressed; it has been suggested that perinatal outcomes in these cases are considerably worse . Alanjari et al reported that the perinatal outcome depends on gestational age at delivery and the degree of FGR, and that normal umbilical artery Doppler at presentation is a favorable prognostic sign. A total of 90.7% (39/43) of cases were identified antenatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las causas de mortalidad se han relacionado con la prematuridad extrema y con el RCIU con Doppler anormal de la arteria umbilical (AU) (3).…”
Section: Discussionunclassified